PENAFSIRAN LABANAN KHĀLIṢAN PERSPEKTIF Al-QUR’AN DAN SAINS DALAM SURAH AN-NAHL AYAT 66 - Ahmad Mujahid; Akhmad Kamal, Maulana Jainal Abidin, Yanor (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
This study explores the meaning of Labanan Khalisan (pure milk) in Surah An-Nahl verse 66 through a scientific interpretation approach. This verse highlights the miracle of milk creation by Allah SWT from the stomachs of livestock, situated between blood and waste, yet producing a pure and easily consumable liquid. This research employs a qualitative-descriptive method based on library research, analyzing various classical and contemporary tafsir sources, along with scientific literature related to the biological process of milk formation. The findings reveal that the formation of milk involves complex digestive and circulatory mechanisms, which can be scientifically explained through the physiology of ruminant animals. The high nutritional value of milk underscores the wisdom and power of Allah SWT as conveyed in the Qur'an. Therefore, Surah An-Nahl verse 66 serves not only as a spiritual lesson but also as a scientific inspiration regarding the creation and benefits of milk in human life